Influence of hole transport layers on internal absorption, charge recombination and collection in HC(NH2)2PbI3 perovskite solar cells. Issue 17 (18th April 2018) - Liu, Yang; Zhang, Hao; Zhang, Yuping; Xu, Bin; Liu, Leijing; Chen, Gang; Im, Chan; Tian, Wenjing
Abstract : The internal absorption, charge recombination and collection in HC(NH2 )2 PbI3 (FAPbI3 ) perovskite solar cells with P3HT and spiro-OMeTAD as the HTL are investigated. The results show that the HTL can affect the internal absorption spectra of the perovskite layers, and spiro-OMeTAD HTL is beneficial for reducing the recombination and enhancing the charge collection in PeSCs. Abstract : A comprehensive study of the internal absorption, charge recombination and collection in HC(NH2 )2 PbI3 (FAPbI3 ) perovskite solar cells (PeSCs) with poly(3-hexylthiophene-2, 5-diyl) (P3HT) and 2, 2′, 7, 7′-tetrakis( N, N -di- p -methoxyphenyl-amino)-9, 9′-spirobifluorene (spiro-OMeTAD) as the hole transport layers (HTLs) is presented. The optical simulation shows that the optical-field distribution and internal absorption of the perovskite layer are different in the cavity region for wavelength > 500 nm in PeSCs with HTLs of P3HT and spiro-OMeTAD. The transient photo-current (TPC) and photoinduced charge extraction by linearly increasing voltage (photo-CELIV) investigations reveal that the charge recombination in PeSCs is much better restrained by using spiro-OMeTAD as the HTL. The light intensity dependent J – V performance indicates that spiro-OMeTAD is more favorable for efficient charge collection due to its suppressed charge recombination. These results manifest that the HTL can affect the internal absorption of the perovskite layer, and the spiro-OMeTAD HTL is beneficial for reducing the recombination and enhancing the charge collection in PeSCs.